THE ISSUE OF FAMILY AND FAMILY VALUES IN UZBEK-KOREAN FOLKLORE (Scientific journal of the Fergana State University, 2023)
This article focuses on family and family values, exploring typological similarities that have emerged in some Uzbek-Korean folklore and fairytales.